SUSTAINABILITY GASTRONOMY IN OPTIMIZING FRAGARIA AS A LOCAL SUPERFOOD USING LOW TEMPERATURE COOKING TECHNOLOGY - Nisa Rahmaniyah Utami; Sri Endah Yuwantiningrum; Marwan Effendy; Nazla Nur Aini; M. Rifal Maulana; Ratu Ainurisa Chasanah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Sustainable gastronomy emphasizes culinary practices oriented towards health, environmental sustainability, and local economic empowerment. This study aims to optimize the potential of Fragaria (strawberries) as a local superfood through the application of Low Temperature Cooking (LTC) technology in cake production. The method used is a true experimental design with a Quantitative Descriptive Analysis (QDA) approach, involving a control group and a treatment group using the LTC technique. The products were organoleptically tested by 35 panelists, consisting of expert and non-expert panelists, for four main sensory attributes: taste, aroma, color, and texture. The results showed that the LTC technique was able to maintain the sensory characteristics and nutritional quality of the product better than conventional methods. The best formulation was obtained at a composition of 75% strawberry puree (P2) with an average score of 3.6, indicating a high level of preference for taste, color, and texture attributes. This study confirms that the application of LTC technology to Fragaria-based products not only increases the competitiveness of local gastronomy but also supports the principles of a circular economy and energy efficiency in the sustainable culinary industry. These findings are expected to serve as a reference for developing functional food products based on locally sourced ingredients with high nutritional value and that are environmentally friendly.